The poetry of Displacement in the novel TAALA ... WAJAA MALIK by Hamid Alrubaieein - Jabar, Kawther M. A. M. (Humanities Journal of University of Zakho, 2013)
Most of the tides that depend on discourse or thesis as a basic to define the style goes into a theoretical measurement which is like a common element among them is the concept of deviation that composes a strong stylistic base a corner brick for lots of stylistic writing that has taken the style of deviation as a parallel name to the literary style. Deviation is an intended error done by the author by which he goes out from the formal expressing style and the linguistic rules that are criteria used by people .This phenomenon is the result of using this genius language which allows the user and the speaker to stay away from the formal are causing a disturbance that becomes a new system in literary text.We are used to see this deviation in the poetic language but we can also find it language of novels and prose that expresses in an indirect way or takes a specific style that goes out of the normal linguistic system, and here was our choice of the novel of (TAALA ... WAJAA MALIK ) written by H-Alrubaieein a language which is neither vernacular nora complete standard in linguistic and rhetorical structure that is used by “ Al-Buhtry “ and writers of “ Moualiqat “ as much he has used the clear , easy language that expresses inferiority of the human being that lives now in the streets of Baghdad or anywhere else in Iraq , and he can transform his cultural power and the stored inheritances as well as being able to express oneself through linguistic Arabic terms , using also intensified seen or sentence and sentences that are poetic in expression and this is what the research confirms that seas in the language of novel such a simple language which gets so close to poetic in its intensity and the accurateness of its description with its enormous deviation from the standard language as it suits the character of the heroine (Salima)that breaks most of society’s chains and obsticales in her life and this is so clear through her language secondly after it has been explained clearly through what she narrates from the events that has lived with the strange man (Malik) who overcomes his pain ;little by little in the novel until he made it to the new life in his motherland and in the shadow of his favorite tree .